What is the overlap between HIV and shigellosis epidemics in England: further evidence of MSM transmission?. (10th May 2017) - Mohan, Keerthi; Hibbert, Matthew; Rooney, Graeme; Canvin, Malcolm; Childs, Tristan; Jenkins, Claire; Simms, Ian; Kirwan, Peter; Delpech, Valerie; Yin, Zheng; Hughes, Gwenda; Field, Nigel
Abstract : Background: Evidence suggests that sexual transmission between men has replaced foreign travel as the predominant mode of Shigella transmission in England. However, sexuality and HIV status are not routinely recorded for laboratory-reported Shigella, and the role of HIV in the Shigella epidemic is not well understood. Methods: The Modular Open Laboratory Information System containing all Shigella cases reported to Public Health England (PHE) and the PHE HIV and AIDS Reporting System holding all adults living with diagnosed HIV in England were matched using a combination of Soundex code, date of birth and gender. Results: From 2004 to 2015, 88 664 patients were living with HIV, and 10 269 Shigella cases were reported in England; 9% (873/10 269) of Shigella cases were diagnosed with HIV, of which 93% (815/873) were in men. Shigella cases without reported travel history were more likely to be living with HIV than those who had travelled (14% (751/5427) vs 3% (134/4854); p<0.01). From 2004 to 2015, the incidence of Shigella in men with HIV rose from 47/100 000 to 226/100 000 (p<0.01) peaking in 2014 at 265/100 000, but remained low in women throughout the study period (0–24/100 000). Among Shigella cases without travel and with HIV, 91% (657/720) were men who have sex with men (MSM). HIV preceded Shigella diagnosis in 86% (610/720), and 65% (237/362) had an undetectable viral load (<50 copies/mL). Discussion: We observed a sustained increase in the national rate of shigellosis in MSM with HIV, who may experience more serious clinical disease. Sexual history, HIV status and STI risk might require sensitive investigation in men presenting with gastroenteritis.